2021
DOI: 10.1172/jci.insight.151872
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of comorbidity heterogeneity among 13,667 patients with hidradenitis suppurativa

Abstract: Hidradenitis suppurativa (HS) is a chronic, inflammatory skin disorder characterized by recurrent abscesses in the groin and flexural areas. HS is associated with a wide range of comorbidities that complicate the disease course. Although these comorbidities have been well-described, it remains unclear how these comorbidities co-associate and whether comorbidity profiles affect disease trajectory. In addition, it is unknown how comorbidity associations are modulated by race and gender. In this comprehensive ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Acne was chosen as a common comorbidity of HS (Hua et al, 2021), which has been associated with plasma cell infiltration into the skin (Carlavan et al, 2018), while AD is an unrelated inflammatory skin disease that nevertheless accompanies lymphadenopathy (Spergel and Paller, 2003) and changes in the B cell compartment (Czarnowicki et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Acne was chosen as a common comorbidity of HS (Hua et al, 2021), which has been associated with plasma cell infiltration into the skin (Carlavan et al, 2018), while AD is an unrelated inflammatory skin disease that nevertheless accompanies lymphadenopathy (Spergel and Paller, 2003) and changes in the B cell compartment (Czarnowicki et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…After the screening process excluding ineligible studies, we included 10 observational studies for critical appraisal. This includes 3 cohort studies ( 15 17 ), 1 case-control study ( 11 ) and 6 cross-sectional studies ( 10 , 12 , 18 21 ). Within the included studies, only one of them were originated from Asia, whereas most of the studies were originated from Europe (4out of 10 studies) and the United States (5 out of 10 studies).…”
Section: Resultsmentioning
confidence: 99%
“…The present study demonstrated that patients with HS have a 2-3 times the risk of being affected with psoriasis. Among the extracted articles, the strongest correlation was observed in a study of 13,667 HS patients where there is three times the risk of developing psoriasis compared to controls ( 18 ). Moreover, in the stratification of gender, both male and female patients with HS presented the trend of higher psoriasis risk.…”
Section: Discussionmentioning
confidence: 99%
“…In this systematic review, five main contributors to HS pathophysiology were addressed: genetics, immunity, microbiome, and endocrinology, together with the identification of risk factors/comorbidities. Mutations in genes encoding gamma-secretase, an intramembrane protease complex, are among the most commonly dities associated with HS were acne, polycystic ovary syndrome, pilonidal sinus, metabolic syndrome, autoimmune disease, and mental health disorders 110 .…”
Section: Discussionmentioning
confidence: 99%
“…Different comorbidities have been linked to HS and could complicate the course of the disease 85,86,96,97,[105][106][107][108][109][110][111] . Comprehensive analysis showed that the main comorbi-…”
Section: (Continues)mentioning
confidence: 99%